Evaluation Of Credit Risk Management On People's Business Loans Of Bank X In Bengkulu Province Using Risk Maturity Model - Adista Anbarani Putri Zaman; Vera Diyanty (UNIVED Press, 2025)
This study aims to analyze the application of risk management to “Kredit Usaha Rakyat” on Bank X in Bengkulu Province to minimize credit risk. This study using qualitative research with descriptive method based on the case study of risk management applied in Bank X to the “Kredit Usaha Rakyat” program. Data collection was carried out by interviewing the entity’s officer and by collecting and analyzing secondary data such as annual report and applicable regulation. Based on analysis using COSO ERM framework, concluded that Bank X has implemented an effective risk management. This study contributes to the field of risk management of banking industry which provide business credit for Micro, Small, and Medium Enterprise (MSME).